TAMPILAN DINAMIS PADA SUMBER DAYA STRATEGIS DAN KEMAMPUAN MENERAPKAN LITERATUR STRATEGI MANUFAKTUR - Affandy Agusman Aris (Jurnal Bisnis dan Kewirausahaan, 2016)
The purpose of this paper is to demonstrate the usefulness of dynamic analysis of the development and management of strategic capabilities and resources in the field of manufaktur.Hal aims to bring the resource system / dynamic capability as a means to understand the problems of the manufacturing strategy. The strategy used to describe an approach that is mainly based on the dynamics of strategy Warren. Extension of this approach diperkenalkan.Temuan - Diagram of dynamic resource / systems capability is a valuable tool to understand the issues that are interconnected and changing the strategic resources and capabilities. Resources and capabilities can be defined as a share in a dynamic simulation model to follow the idea of ​​the dynamics of research sistem.Keterbatasan/implications - The nature of strategic capabilities and relationships they need to be investigated further. The approach needs to be developed to measure and to measure these concepts. The relationship between the winner of order / qualifications and the inflow / outflow of capabilities and resources stocks should be examined more practical lanjut.Implikasi - static analysis of strategic issues that are often difficult to interpret. The dynamic nature of strategic issues that need to be reflected in the tools used to analyze them. Originality / value - Applies dynamic analysis to manufacturing strategy and use a textbook example of this new way to describe the relevance of the approach.